Domestication, diversity and use of Brassica oleracea L., based on ancient Greek and Latin texts - Maggioni, L.; Bothmer, R. von; Poulsen, G.; Lipman, E. (Springer, 2018)
The domestication process of Brassica oleracea L. has not been fully clarified, either regarding its initial location or the progenitor species involved. Two alternative hypotheses proposed so far point to either a northwest European or a Mediterranean location. Previous studies to clarify the domestication process focused on linguistic aspects and on the earliest occurrences in ancient literature of words referring to B. oleracea. Those studies are here extended to offer a comprehensive account of literary occurrences of the brassica vegetables in ancient Greek and Latin texts, between the VI century B.C.E. and the IV century C.E. This study offers a contribution to ancient ethnobotanical knowledge in the Mediterranean, including agricultural practices and culinary and medicinal uses. It also defines the time when increasing diversity of crop varieties is documented and it adds weight to the hypothesis of a Mediterranean location of the domestication of B. oleracea.